Analysis of Organizational Culture and Time Management on the Performance of State Civil Apparatus moderated by the Variable Work Capability at the Village Community Empowerment Service in South Sulawesi Province - Nisma Iriani; Rahmuniar Rahmuniar; Arjang Arjang; Syahribulan Syahribulan (Universitas Dharma Wacana, 2022)
The purpose of this study was to analyze the effect of organizational culture and time management on the work ability and performance of ASN at the Office of the Village Community Empowerment Service in South Sulawesi Province.The study used a sample of 111 State Civil Apparatus at the Office of Community and Village Empowerment Services in South Sulawesi Province.The sampling technique used probability sampling with purposive sampling. The data collection technique used in this study was a questionnaire . This study used quantitative data analysis techniques using path analysis.The results of this study state that organizational culture and time management have a direct positive and significant effect on work ability and performance of the State Civil Apparatus, then time management has an effect on work capability. It is also known that work ability has a significant effect on employee performance, while organizational culture and management time has a positive and significant effect on performance through the work capability of the State Civil Apparatus at the Office of the Village Community Empowerment Service in South Sulawesi Province.